Analysis of total plate count and fungus yeast of mahkota dewa fruit as raw material for making syrup. (April 2020) - Winarni, S; Arifan, F; Setyawan, A; Nurdiana, A; Windari
Abstract: Mahkota Dewa (Phaleria macrocarpa L.) or Simalakama plants are native plants from Papua. The Mahkota Dewa fruit can be used to treat various diseases ranging from flu, rheumatism, lungs, cirrhosis of the liver to cancer. The Mahkota Dewa fruit contains alkaloids, saponins, and flavonoids. The presence of flavonoids in the fruit of this plant can be used as an antioxidant. One of the innovations in the use of this fruit is m turn fruit into syrup. Syrup manufacturing process has several stages, namely by choosing the fruit that is ripe and dried first. The Mahkota Dewa syrup from Tazakka in Pledokan Village, Sumowono Subdistrict still uses direct sunlight during the drying process. This study aims to determine the bacterial content of the dried fruit of the Mahkota Dewa with the sun and dry with the oven so that producers can still use the oven aids if the results are not much different. The test site is located in Peldokan Village, Sumowono District, Central Java Medical Laboratory and Medical Devices Testing and Diponegoro University Semarang. The materials and tools used are the mature Mahkota Dewa, tray, oven, dried fruit Mahkota Dewa and oven, the crown god syrup sample, and laboratory equipment. Bacterial testing uses the TPC (Total Plate Count) and Fungus Yeast methods. Based on the results of the bacteriological test analysis of the dried fruit Mahkota Dewa it is known that the number of general germs or TPC and Fungus Yeast in oven dried fruit is more than that of the sun dried which is 1.8 × 10 5 CFU / gram and 3.9 × 10 4 CFU / gram. The proximate content of the Mahkota Dewa syrup is 1.43% protein, 0.09% fat, 70.16% carbohydrate, 28.18% water content and 0.14% ash content.